Geographical analysis of tourist and service attractions and the possibilities of developing them in Qastal Maaf district - ناصر, لميس (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
Qastal Maaf is a district in the Lattakia region, rich in both natural and human tourist attractions. The districts natural diversity, ranging from tourists and mountains to the Mediterranean sea and the archaeological sites, creates a unique tourist environment, the tourism services sector occupies a complementary system of tourist attractions and the demand for it is increasing because it is one of the fields industry. Attracting public and private investments to tourist attraction and developing the tourism services sector ensures the continuity of tourism to the Qastal Maaf district this contributes to providing job opportunities for the local population thus improving their standard of living and developing the district economically and socially. The spatial- geographical analysis of natural and human touristic attractions was studied in the Qastal Maaf. The effect of tourism on the local environment, the productive services and the economic activities such as agriculture, industry and tourism activity in it with the aim of developing them, and put the future plans. Wadi Qandil had the touristic attractions by 28% the lowest percentage was in the Alisawea 5%. Zaerin was one of the most important location because of restaurants that suit the middle-income tourists. The diversity of economic activities contributes to the development of tourism and 50% of tourists confirmed that the level of services was poor. The roads in Wadi Qandil and Zaerin were poor at 26% and the electricity was 66%.The water service was poor at 64% due to its impact on the electricity while the communications and clearing services were acceptable at 52%.